Assessment of safety in hepatic resection for hepatocellular carcinoma focusing on indirect hyperbilirubinemia. Issue 3 (March 2013) - Masuda, Toshiro; Beppu, Toru; Nakagawa, Shigeki; Okabe, Hirohisa; Chikamoto, Akira; Miyata, Tatsunori; Mima, Kosuke; Otao, Ryu; Hayashi, Hiromitsu; Doi, Koichi; Ishiko, Takatoshi; Takamori, Hiroshi; et al.
Abstract Background/purpose The indications for hepatic resection for hepatocellular carcinoma (HCC) patients with total bilirubin (T‐Bil) equal to or higher than 1.2 mg/dl remain controversial. The aim of this study was to investigate the safety of hepatic resection for HCC patients who showed high T‐Bil (≥1.2 mg/dl) with low direct bilirubin (D‐Bil ≥ 0.5 mg/dl). Methods Thirty‐four HCC patients showing high T‐Bil with low D‐Bil were treated with mono‐ to tri‐segmentectomy between January 2000 and December 2010. The perioperative clinical parameters and prognosis of the high T‐Bil/low D‐Bil patients were compared with those of 253 HCC patients showing normal T‐Bil. In addition, complication rates of the patients with high T‐Bil/high D‐Bil (n = 4) were analyzed. Results The prothrombin time activity, indocyanine green clearance test, asialo‐scintigraphy, and platelet count were similar in the two groups. The mean serum albumin in high T‐Bil/low D‐Bil patients was significantly higher than that of normal T‐Bil patients (4.2 ± 0.5 vs. 4.0 ± 0.4 g/dl, P = 0.004). There were no significant differences in operation time, intraoperative bleeding, red cell concentrate transfusion rate, postoperative complication rate, and disease‐free and overall survivals between the two groups. Postoperative hyperbilirubinemia (T‐Bil >5 mg/dl) with ascites was observed in one of four high T‐Bil/high D‐Bil patients (25 %). Conclusions Mono‐ to tri‐segmentectomy can be performed in patients with low D‐Bil (≥0.5 mg/dl) similarly to patients with low T‐Bil (<1.2 mg/dl), even in HCC patients showing high T‐Bil (≥1.2 mg/dl).